Learning effect on perinatal post‐mortem magnetic resonance imaging reporting: single reporter diagnostic accuracy of 200 cases. (23rd May 2017) - Ashwin, Clare; Hutchinson, J. Ciaran; Kang, Xin; Langan, Dean; Jones, Rod; Norman, Wendy; Cannie, Mieke; Jani, Jacques; Sebire, Neil J.; Arthurs, Owen J.
Abstract: Objective: The objective of the study is to compare diagnostic accuracy of perinatal post‐mortem magnetic resonance (PMMR) imaging against conventional autopsy, when reported by a single‐blinded observer for all organ systems following a period of initial experience. Methods: We compared pre‐autopsy PMMR with conventional autopsy for the detection of (1) major pathological abnormalities related to the cause of death and (2) all diagnostic findings in five different body organ systems. PMMR was reported blinded to autopsy findings. Results: In 201 cases, 123/146 (84.2%) of major abnormalities were identified by PMMR. Overall diagnostic accuracy of PMMR was 89.6% [95% confidence interval (CI): 84.3, 93.2%] across all cases, with high concordance 91.8% (95% CI: 89.9, 93.4%) across most organ systems. Our study showed higher concordance than single reporter statistics previously reported in neurological [92.2% vs 73.8%; diff 18.4% (95% CI: 11.0, 25.4%) p  < 0.01] and thoracic systems [93.7% vs 81.2%; diff 12.5% (95% CI: 6.3, 18.4%) p  < 0.01] and slightly better overall [91.8% vs 87.1%; diff 4.7% (95% CI: 2.1, 7.3%) p  < 0.01]. Conclusion: The PMMR examinations can be reliably reported by a single radiologist, following a period of experience and training with this specific modality, with high‐diagnostic accuracy for all organ systems. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Post‐mortem magnetic resonance (PMMR) imaging is becoming an accepted part of minimally invasive autopsy examinations where parents decline invasive examinations. PMMR has a high concordance with autopsy for detecting most fetal pathology. What does this study add? Perinatal PMMR examinations can be reliably reported by a single‐trained radiologist reflecting everyday clinical practice. PMMR has high diagnostic accuracy when previous training is performed, particularly for neurological and abdominal abnormalities. The high overall negative predictive value supports the use of PMMR as a screening tool and will play an important role for parents in whom standard autopsy is unacceptable.